2015
DOI: 10.18632/oncotarget.3706
|View full text |Cite
|
Sign up to set email alerts
|

Maritoclax and dinaciclib inhibit MCL-1 activity and induce apoptosis in both a MCL-1-dependent and -independent manner

Abstract: The anti-apoptotic BCL-2 family proteins are important targets for cancer chemotherapy. Specific and potent inhibitors of the BCL-2 family, such as ABT-263 (navitoclax) and ABT-199, are only effective against some members of the BCL-2 family but do not target MCL-1, which is commonly amplified in tumors and associated with chemoresistance. In this report, the selectivity and potency of two putative MCL-1 inhibitors, dinaciclib and maritoclax, were assessed. Although both compounds induced Bax/Bak- and caspase-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 47 publications
5
41
0
Order By: Relevance
“…reports showing that MCL-1 expression was decreased by dinaciclib in various cancer cells (Chen, et al 2015, Fu, et al 2011, Gregory, et al 2015, Varadarajan, et al 2015. As shown in Figure 3F, we confirmed that dinaciclib inhibited both MCL-1 and BCL-xL in stimulated primary cells and MEC-1.…”
Section: Dinaciclib Inhibits Pro-survival Signals In Cll Cellssupporting
confidence: 78%
“…reports showing that MCL-1 expression was decreased by dinaciclib in various cancer cells (Chen, et al 2015, Fu, et al 2011, Gregory, et al 2015, Varadarajan, et al 2015. As shown in Figure 3F, we confirmed that dinaciclib inhibited both MCL-1 and BCL-xL in stimulated primary cells and MEC-1.…”
Section: Dinaciclib Inhibits Pro-survival Signals In Cll Cellssupporting
confidence: 78%
“…Thus, while Marinopyrrole A sensitivity correlates with BCL2 family protein expression profile, it is clearly not a specific MCL1 inhibitor. Altogether, our results are in agreement with other reports showing that Marinopyrrole A fails to show strict selective cytotoxicity for MCL1‐dependent cell lines (Eichhorn et al , ; Varadarajan et al , ). Given that MCL1 level is known to be an important chemoresistance factor, particularly for BH3 mimetic drugs, such as Navitoclax and Venetoclax (Bodet et al , ), the ability of Marinopyrrole A to decrease MCL1 levels by multiple mechanisms suggests that it will be an interesting compound to enhance drug efficiency, as previously demonstrated in melanoma cells (Pandey et al , ).…”
supporting
confidence: 94%
“…[126] Maritoclax was reported to be a selective MCL-1 antagonist able to disrupt the BIM-MCL-1 interaction and promote proteasomal degradation of MCL-1 that markedly enhanced the efficacy of ABT-737 against multiple hematologic malignancies,[127] but subsequent studies have shown that the compound likely also acts through mechanisms independent of MCL-1. [128] Of the early putative MCL-1 inhibitors, TW-37 is one that induces apoptosis in a BAK-dependent manner in cells that require MCL-1 for survival, but apoptosis induced by TW-37 is also, in part, dependent on NOXA. [129] (-)BI97D6 is a pan-BCL-2 family inhibitor that was shown to disrupt Mcl-1/Bim and Bcl-2/Bax interactions and induce BAX/BAK-dependent apoptosis in AML cells, overcoming MCL-1-mediated resistance as well as extrinsic, microenvironmental resistance.…”
Section: Novel Compounds That Inhibit Bcl-xl or Mcl-1mentioning
confidence: 99%